ORal anticoagulants In fraGile patients with percutAneous endoscopic gastrostoMy and atrIal fibrillation: the (ORIGAMI) study. Issue 3 (12th March 2021) - D'Amario, Domenico; Galli, Mattia; Canonico, Francesco; Restivo, Attilio; Arcudi, Alessandra; Scacciavillani, Roberto; Cappannoli, Luigi; Riccioni, Maria Elena; Annetta, Maria Giuseppina; Di Stefano, Gaetano; Piccinni, Carlo; Vergallo, Rocco; et al.
Abstract : Aims: The ORal anticoagulants In fraGile patients with percutAneous endoscopic gastrostoMy and atrIal fibrillation (ORIGAMI) study investigates the safety and efficacy of Edoxaban administered via PEG in patients with atrial fibrillation and a clinical indication for a long-term anticoagulation. Design: In this prospective, single-centre observational study, 12 PEG-treated patients with indication to anticoagulation will receive edoxaban via PEG and will be followed up to 6 months. Plasma antifactor Xa activity and edoxaban concentrations will be assessed. Thromboembolic (ischaemic stroke, systemic embolism, venous thromboembolism) and bleeding events (Bleeding Academic Research Consortium and Thrombolysis in Myocardial Infarction) will be recorded at 1 and 6 months. Preliminary results: A retrospective analysis of five atrial fibrillation cases undergoing PEG implantation at our Institution who received edoxaban via PEG showed plasma anti-FXa levels at a steady state of 146 ± 15 ng/ml, without major adverse event at a mean follow-up of 6 months. Conclusion: ORIGAMI prospectively investigates PEG-administration of edoxaban in PEG-treated patients requiring long-term anticoagulation. Our preliminary retrospective data support this route of DOAC administration. ClinicalTrials.gov Identifier: NCT04271293